Efficacy of Application of Dietary Supplements in Acute Intoxication - Z.B. Yessimsiitova; Saparov Kuandyk; Y. Sinyavskiy; G. Tussupbekova; N. Ablaikhanova; A. Kozhamzarova; Ablaikhanova Nurzat; Ussenova Gauhar; Turlybekov Murat (Journal of Pharmacy and Nutrition Sciences, 2019)
The effectiveness of BAA balsam "Revival plus" as a means of pharmacological correction of neurotoxic and hepatotoxic lesions as consequences of acute ethanol poisoning was evaluated. It has been established that in the conditions of acute severe intoxication ethanol BAA balsam "Revival plus" has pharmacological efficacy in terms of survival keeping temperature and frequency of respiratory movements in poisoned rats with a therapeutic and prophylactic scheme of their use. Value of the work consists in the experimental substantiation of the possibility of using BAA balsam "Revival plus" as a promising means of treatment of acute extremely severe ethanol poisoning. The aim of this paper is to demonstrate the efficacy of application of dietary supplements in acute intoxication, to depict the effectiveness of balsam during the intoxication, and from scientific purpose to prove the significance of this supplement. The obtained data testify to the effectiveness of the use of bio additives in ethanol poisoning and possible mechanisms for the implementation of the hepatic protective effect of the BAA balsam "Revival Plus" under various life-threatening conditions. The purpose of this research is evaluation of the experimental effectiveness of BAA balsam "Revival Plus" for ethanol poisoning. To achieve this goal the following tasks are set: To reveal the features of the histological structure of the liver of control and experimental rats of the second group with ethanol poisoning; To study the morphological changes in the liver of rats of the third group with ethanol poisoning against the background of the use of BAA balsam "Revival plus"; To study the peculiarities of the action of the BAA balsam "Revival plus" on the biochemical parameters of the blood of rats. Questions about the interaction of dietary supplements and alcoholic beverages are regularly being raised by both researchers and ordinary consumers. In most cases talk about the dangers of dietary supplements for a person who often drinks alcoholic beverages is not necessary.